Combined uphill and downhill sprint running training is more efficacious than horizontal - Paradisis, G. P.; Bissas, A.; Cooke, C. B. (International Journal of Sports Physiology and Performance, 2009)
Purpose: This study examined the effects of sprint running training on sloping surfaces (3°) on selected kinematic and physiological variables. Methods: Fifty-four sport and physical education students were randomly allocated to one of two training groups (combined uphill-downhill [U+D] and horizontal (H)) and a control group (C). Pre- and posttraining tests were performed to examine the effects of 8 wk of training on the maximum running speed (MRS), step rate, step length, step time, contact time, eccentric and concentric phase of contact time (EP, CP), flight time, selected posture characteristics of the step cycle, and 6-s maximal cycle sprint test. Results: MRS, step rate, contact time, and step time were improved significantly in a 35-m sprint test for the U+D group (P < .01) after training by 4.3%, 4.3%, -5.1%, and -3.9% respectively, whereas the H group showed smaller improvements, (1.7% (P < .05), 1.2% (P < .01), 1.7% (P < .01), and 1.2% (P < .01) respectively). There were no significant changes in the C group. The posture characteristics and the peak anaerobic power (AWT) performance did not change with training in any of the groups. Conclusion: The U+D training method was significantly more effective in improving MRS and the kinematic characteristics of sprint running than a traditional horizontal training method.